2018
DOI: 10.15203/ozp.2730.vol47iss3
|View full text |Cite
|
Sign up to set email alerts
|

Societal Relevance Dimensions of Graduating in Political Science in Austria

Abstract: 4,350 students were enrolled in a BA and 1,481 pursued a Master’s programme in political science in Austria in 2016. However, only a small number of degree holders embark on an academic career; many more move on to jobs in the public or private sector. In this contribution we focus on the impact of teaching political science and the contribution that political science graduates make to society. The article draws on data from the Graduate Monitoring which evaluates graduates’ progress in the labour market, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Research has revealed that many social sciences graduates work long hours, have heavy workloads, experience stress, face burnout, and are likely to encounter a mismatch between their abilities and job requirements [13,[16][17][18][19]. In line with that, there is empirical evidence showing that social sciences graduates are more often dissatisfied with their jobs or careers in general compared to graduates from applied fields (e.g., [20,21]). All these negative aspects and experiences can deteriorate their well-being [22] and performance at work [23], thereby threatening the sustainability of their careers [9].…”
Section: Introductionmentioning
confidence: 89%
“…Research has revealed that many social sciences graduates work long hours, have heavy workloads, experience stress, face burnout, and are likely to encounter a mismatch between their abilities and job requirements [13,[16][17][18][19]. In line with that, there is empirical evidence showing that social sciences graduates are more often dissatisfied with their jobs or careers in general compared to graduates from applied fields (e.g., [20,21]). All these negative aspects and experiences can deteriorate their well-being [22] and performance at work [23], thereby threatening the sustainability of their careers [9].…”
Section: Introductionmentioning
confidence: 89%
“…For the employer side, scholars would have to work with questionnaires or interviews to uncover which images of and experiences with political science graduates employers are holding and whether a degree in political science increases or decreases the chances of graduates to get hired. For the employee side, and as the contribution by Gatt et al (2018) in this issue demonstrates, scholars would have to collect and evaluate statistical data on income, rate and duration of unemployment, and rates of employment in different job sectors to get a handle on the overall situation of graduates in the job market. In addition, they would have to use questionnaires or interviews to analyze how graduates experience the added value of their academic degree, networks, skills, and knowledge.…”
Section: The Concept Of Relevancementioning
confidence: 99%